Cognitive function and psychological well-being in older adults with sensorineural hearing loss: An Egyptian perspective - Heba G. Saber; Fathy N. Fatouh; Anas Askoura; Ghada O. Wassif; Enas R. Mohamed (Clinical Epidemiology and Global Health)
Background: Sensorineural hearing loss (SNHL) is a common condition among older adults and is increasingly recognized as a risk factor for cognitive decline and psychological distress. Hearing impairment can lead to reduced social engagement, functional limitations, and a higher risk of depression, negatively impacting quality of life. This study investigates the cognitive function and psychological well-being of older Egyptians with SNHL by assessing their daily activity performance and mental health status. Methods: A cross-sectional study was conducted among 114 participants aged 60 years or older diagnosed with SNHL using Pure Tone Audiometry (PTA). Functional and psychological assessments were performed using the Activities of Daily Living (ADL), Instrumental Activities of Daily Living (IADL), and the Geriatric Depression Scale (GDS) to evaluate independence and mental health. Results: SNHL severity was significantly associated with age, lower education, smoking, diabetes, hypertension, and ototoxic drug use. Functional impairments (ADL/IADL) and depression were strongly linked to SNHL, underscoring its impact on independence and mental health. Ordinal regression confirmed hypertension and ototoxic drug exposure as key predictors of SNHL severity. Conclusion: & Recommendations: SNHL severity is significantly associated with demographic, clinical, and functional factors, reinforcing its impact on cognitive function and psychological well-being in older adults. Early screening, particularly for high-risk individuals with chronic conditions, is crucial. Preventive strategies such as blood pressure control, cautious use of ototoxic drugs, and hearing conservation programs are recommended to reduce SNHL-related health burdens and improve the quality of life for older adults.